Size effect and lateral pressure effect on the mechanical resistance of columnar jointed basalt - Wang, Yong-yi; Gong, Bin; Tang, Chun-an; Yang, Xiao-yu (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2023)
To reveal the size effect and lateral pressure effect of columnar jointed basalts (CJBs), the meso-damage mechanics, statistical strength theory, continuum mechanics and digital image correlation are combined, and a series of heterogeneous numerical models of CJBs orthogonal and parallel to column axis are established. The elastic modulus, Poisson's ratio, uniaxial compressive strength, friction angle, residual strength coefficient, heterogeneity index of basalts 60 GPa, 0.2, 120 MPa, 56.15°, 0.1 and 5, respectively. The gradual fracture processes and acoustic emission characteristics of CJBs suffering various lateral pressures are numerically simulated under the axial loading rate of 0.05 mm/min, and the influence of model size on the anisotropy and lateral pressure effect of CJBs is analyzed. The results show that: for the direction I/Ⅱ orthogonal to column axis, when the lateral pressure is 2 MPa and 6 MPa, the critical value of size effect is 4 m and 6 m, respectively; for the direction parallel to column axis, the compressive strength of specimen can be obviously improved by increasing lateral pressure for the certain sizes; when the lateral pressure is 6 MPa and the distance ratio of the secondary joint set is 0% or 50%, the compression strengths of the 3 m and 6 m specimens change in a U-shape and a V-shape with the column dip angle increasing, respectively. The results can contribute to understanding the non-linear deformation and failure behaviors of CJBs. •The digital image correlation, meso-damage mechanics, statistical strength theory and continuum mechanics are combined.•The fracture mechanism and AE energy evolution characteristics of columnar jointed basalts are revealed.•The size effect for CJBs under different lateral pressures is discussed.•The influence of column dip angle, residual strength, irregularity, model boundaries, etc., is analyzed.